2001
DOI: 10.1152/jn.2001.85.6.2630
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Muscle Stiffness in the Control of Balance During Quiet Standing

Abstract: This research presents new data and reanalyzed information to refute the criticisms of our model of stiffness control during quiet standing. A re-review of their references to biomechanical research on muscle ankle stiffness confirmed muscle stiffness estimates of the ankle series elastic elements that agreed closely with our estimates. A new technique is presented that directly estimates the muscle stiffness from the ankle moment (N. m) and sway angle (deg). The linear regression of 10 subjects standing quiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
166
1
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(189 citation statements)
references
References 12 publications
11
166
1
11
Order By: Relevance
“…The nonlinear property of SDEs is important although the concept of simple muscle stiffness control during quiet standing has been accepted for a long time [16,17]. However, the linear model [8][9][10] has been rejected by the experimental results of the relationship between the body posture angle and the ankle torque [18,19], and the postural instability, which is called "microfall" [20].…”
Section: Discussionmentioning
confidence: 99%
“…The nonlinear property of SDEs is important although the concept of simple muscle stiffness control during quiet standing has been accepted for a long time [16,17]. However, the linear model [8][9][10] has been rejected by the experimental results of the relationship between the body posture angle and the ankle torque [18,19], and the postural instability, which is called "microfall" [20].…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in preferences of the ankle strategy in this movement plane can be caused by tiredness [14], which, in consequence, can result in deterioration in stability. However, in some works, like in our research, it was observed that there was a more considerable increase in sways after an effort in the frontal plane than in the sagittal one.…”
Section: Discussionmentioning
confidence: 99%
“…In a standing position, in order to keep or recover balance it is possible to apply two strategies depending on the degree of its disturbance: an ankle or a hip joint [12][13][14]. One strategy refers to a minor balance distur bance and it is initiated by a contraction of ankle musc les.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large numbers of publication work [1][2][3][4] at the equilibrium stability of upright standing were based on the simple biomechanical model of the human body as single inverted pendulum. The multi-joint properties of the body were rarely taken into account in the previous studies.…”
Section: Introductionmentioning
confidence: 99%